PENGARUH NET WORKING CAPITAL, DIVIDEND PAYMENT, CASH CONVERSION CYCLE, DAN OPERATING CASH FLOW TERHADAP CASH HOLDING PERUSAHAAN - INDRA PRASETYO, LAXMANA (Jurnal Akuntansi AKUNESA, 2017)
Retaining cash in the optimal point is very important towards the continuation of an organization or a company. In some articles mentioned that "cash is king" that mean the cash have a high value, and cash is more valuable than assets. This research focuses on the factors that affect the cash holding of manufacturing company in Indonesia that registered in BEI 2012-2016. Furthermore, analysis using a stratified random sampling method, the results show that cash holding companies affected by net working capital and operating cash flow, while the dividend payment and cash conversion cycle does not affect  company cash holding. Keywords: Cash holding, Net working capital, Dividend payment, Cash conversion cycle, Operating cash flow